Physical Insights on MILD Combustion From DNS - Swaminathan, N. (Frontiers in Mechanical Engineering, 2019)
MILD combustion is gaining interest in recent times because it is attractive for green combustion technology. However, its fundamental aspects are not well-understood. Recent progresses made on this topic using direct numerical simulation data are presented and discussed in a broader perspective. It is shown that a revised theory involving at least two chemical timescales is required to describe the inception of this combustion not only showing both autoignition and flame characteristics but also a strong interaction between these two phenomena. The reaction zones have complex morphological and topological features and the most probable shape is pancake-like structure implying micro-volume combustion under MILD conditions unlike the sheet-combustion in conventional cases. Relevance of the MILD (micro-volume) combustion to supersonic combustion is explored theoretically and qualitative support is shown and discussed using experimental and numerical Schlieren images.